Change in Disease Dynamics and Health Care Utilisation in Children during COVID 19 in a Tertiary Care Hospital of Eastern India - Sahoo, Bandya; Kanyari, S. Suneeti; Pradhan, Deepti Damayanty; Patnaik, Sibabratta; Behera, Manas Ranjan (National Journal of Community Medicine, 2022)
This retrospective, observational study was conducted by collecting data from medical records during COVID 19 pandemic from March 2020 till August 2020. This was compared with the data of 2019 during similar months. The impact of COVID 19 on use of preventive and curative paediatric health care service units like outpatient department, casualty, intensive care and immunization clinic were assessed. Data from 2019 to 2020 were compared using standard parametric and nonparametric tests. There was a significant decline in routine OPD (68%) attendance during the COVID 19 period as compared to pre-COVID period. Paediatric ward admissions and PICU admissions were decreased by 55% and 42% respectively. We also observed a significant 43% decline in the number of children attending immunization clinic in the year 2020. The fear of COVID 19 pandemic and the measures taken to control the pandemic has affected the health seeking behaviour of patients. This evaluation of trends in healthcare use may help in planning the delivery of healthcare service delivery in future.